The Cambridge handbook on European monetary, economic and financial market integration/ edited by Dariusz Adamski, Fabian Amtenbrink, Jakob de Haan. - Adamski, Dariusz, 1975-; Haan, Jakob de; Amtenbrink, Fabian (Cambridge University Press, 2023)
This Handbook provides a comprehensive analysis of the past, present, and future of the European Economic and Monetary Union in its broader context. It incorporates economic, legal and political science perspectives to provide an in-depth and forward-looking scrutiny of the rationales, the main features and the shortcomings of the economic, monetary and financial integration in the euro area. Studying its complex, highly interconnected governance structures, the authors suggest directions for necessary reforms. With contributions from a diverse group of leading experts in their fields, this volume is truly versatile in its scope and approach, whilst remaining accessible for readers of different academic backgrounds.